Effectiveness of a targeted brief intervention for recent suicide attempt survivors: a randomised controlled trial protocol. Issue 3 (3rd March 2023) - Pisani, Anthony; Connor, Kenneth; Van Orden, Kimberly; Jordan, Neil; Landes, Sara; Curran, Geoffrey; McDermott, Michael; Ertefaie, Ashkan; Kelberman, Caroline; Ramanathan, Seethalakshmi; Carruthers, Jay; Mossgraber, Kristina; et al.
Abstract : Introduction: Effective, brief, low-cost interventions for suicide attempt survivors are essential to saving lives and achieving the goals of the National Strategy for Suicide Prevention and Zero Suicide. This study aims to examine the effectiveness of the Attempted Suicide Short Intervention Program (ASSIP) in averting suicide reattempts in the United States healthcare system, its psychological mechanisms as predicted by the Interpersonal Theory of Suicide, and the potential implementation costs, barriers and facilitators for delivering it. Methods and analysis: This study is a hybrid type 1 effectiveness–implementation randomised controlled trial (RCT). ASSIP is delivered at three outpatient mental healthcare clinics in New York State. Participant referral sites include three local hospitals with inpatient and comprehensive psychiatric emergency services, and outpatient mental health clinics. Participants include 400 adults who have had a recent suicide attempt. All are randomised to 'Zero Suicide-Usual Care plus ASSIP' or 'Zero Suicide-Usual Care'. Randomisation is stratified by sex and whether the index attempt is a first suicide attempt or not. Participants complete assessments at baseline, 6 weeks, and 3, 6, 12 and, 18 months. The primary outcome is the time from randomisation to the first suicide reattempt. Prior to the RCT, a 23-person open trial took place, in which 13 participants received 'Zero Suicide-Usual Care plus ASSIP' and 14 completed the first follow-up time point. Ethics and dissemination: This study is overseen by the University of Rochester, with single Institutional Review Board (#3353) reliance agreements from Nathan Kline Institute (#1561697) and SUNY Upstate Medical University (#1647538). It has an established Data and Safety Monitoring Board. Results will be published in peer-reviewed academic journals, presented at scientific conferences, and communicated to referral organisations. Clinics considering ASSIP may use a stakeholder report generated by this study, including incremental cost-effectiveness data from the provider point of view. Trial registration number: NCT03894462 .